INCLUSIVE EDUCATION POLICIES: SUPPORTING STUDENTS WITH LEARNING DISABILITIES FOR ACADEMIC SUCCESS (Лучшие интеллектуальные исследования, 2025)
Abstract: Inclusive education policies are essential for ensuring equitable access to education for all students, including those with learning disabilities (LDs). This study explores the impact of inclusive education strategies on the academic success of students with LDs at Uzbekistan State World Languages University. The research employs a pre-test and post-test design, evaluating students' performance before and after implementing inclusive teaching strategies, such as differentiated instruction, assistive technology, and peer mentoring. The findings reveal a significant improvement in academic performance, self-confidence, and classroom engagement among students with LDs.